2011
DOI: 10.1016/j.peptides.2010.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated cholecystokinin-8 activates phospho-mTOR immunoreactive neurons of the paraventricular nucleus in rats

Abstract: The serin/threonin-kinase, mammalian target of rapamycin (mTOR) was detected in the arcuate nucleus (ARC) and paraventricular nucleus of the hypothalamus (PVN) and suggested to play a role in the integration of satiety signals. Since cholecystokinin (CCK) plays a role in the short-term inhibition of food intake and induces c-Fos in PVN neurons, the aim was to determine whether intraperitoneally injected CCK-8S affects the neuronal activity in cells immunoreactive for phospho-mTOR in the PVN. Ad libitum fed mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…To provide additional insights, we examined the localization of mTOR and thyroid hormone receptor in the rat hypothalamus. In keeping with previous observations, our data show that mTOR is highly expressed in key hypothalamic nuclei modulating feeding, such as the ARC, PVH and VMH [25,30,31]. Notably, our localization studies also show that mTOR is highly co-expressed with TRα in the ARC, raising the possibility of direct regulation of mTOR activity by thyroid hormones at this level.…”
Section: Varela Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…To provide additional insights, we examined the localization of mTOR and thyroid hormone receptor in the rat hypothalamus. In keeping with previous observations, our data show that mTOR is highly expressed in key hypothalamic nuclei modulating feeding, such as the ARC, PVH and VMH [25,30,31]. Notably, our localization studies also show that mTOR is highly co-expressed with TRα in the ARC, raising the possibility of direct regulation of mTOR activity by thyroid hormones at this level.…”
Section: Varela Et Almentioning
confidence: 99%
“…Recent evidence has shown that hypothalamic mTOR signalling plays a major role in modulating energy balance [22,[25][26][27][28][29]. In rats, mTOR pathway is highly expressed in specific hypothalamic regions, such as the arcuate (ARC), paraventricular (PVH) and suprachiasmatic (SCN) nuclei [25,30,31]. Within the ARC, mTOR co-localizes with neuropeptide Y (NPY; and thus with agouti-related protein, AgRP [32]) and proopiomelanocortin (POMC) neurons [25,33].…”
Section: Introductionmentioning
confidence: 99%
“…The PVN neurons activated by CCK express cocaine and amphetamine regulated transcript (CART) and phosphor-mammalian target of rapamycin [17,18]. The PVN neurons activated by CCK express cocaine and amphetamine regulated transcript (CART) and phosphor-mammalian target of rapamycin [17,18].…”
Section: Hypothalamic Responses To Peripheral Cholecystokininmentioning
confidence: 99%
“…Cholecystokinin control intestinal motility (Schultzberg et al 1980). Gibbs et al (1973) detected that exogenous CCK prohibits dietary intake and also in rodents (Lembke et al 2011;Bewick 2012;Engster et al 2014). CCK can regulate the contraction of the gallbladder, the secretion and the growth of the pancreas, the gastric emptying, the duodenal secretion, satiety, glucose homoeostasis and insulin secretion (Wattez et al 2013).…”
Section: Cholecystokinin (Cck)mentioning
confidence: 99%